2017
DOI: 10.1038/ncomms15431
|View full text |Cite
|
Sign up to set email alerts
|

Extra-embryonic tissue spreading directs early embryo morphogenesis in killifish

Abstract: The spreading of mesenchymal-like cell layers is critical for embryo morphogenesis and tissue repair, yet we know little of this process in vivo. Here we take advantage of unique developmental features of the non-conventional annual killifish embryo to study the principles underlying tissue spreading in a simple cellular environment, devoid of patterning signals and major morphogenetic cell movements. Using in vivo experimentation and physical modelling we reveal that the extra-embryonic epithelial enveloping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 44 publications
(59 reference statements)
1
59
1
Order By: Relevance
“…Random movements of EL cells in the dispersed phase were originally reported by Lesseps et al, in the '70s [45] by means of bright-field microscopy and were later confirmed by us [6]. instructed by mechanical interactions between EVL and EL cells [8].…”
Section: End Of Epiboly (Ws 19)supporting
confidence: 58%
See 2 more Smart Citations
“…Random movements of EL cells in the dispersed phase were originally reported by Lesseps et al, in the '70s [45] by means of bright-field microscopy and were later confirmed by us [6]. instructed by mechanical interactions between EVL and EL cells [8].…”
Section: End Of Epiboly (Ws 19)supporting
confidence: 58%
“…It is known that diapause II is characterized by reduced protein synthesis, cell cycle arrest and remodelling of mitochondrial physiology and it is controlled by insulin-like growth factor 1 signalling [29][30][31][32][33][34][35].Recently, RNAseq studies have shown that , gene-expression patterns during diapause resemble those observed during aging [36] and vitamin D signalling controls to the choice between direct development and diapause II [37]. While early embryonic development following fertilisation have been in part studied [7][8][9], the characterization of the physiological and molecular events occurring during diapause I has been started to be investigated only recently [35,38,39]. Here, to investigate entry and exit form diapause I and II, we created a stable transgenic line in N. furzeri that expresses fluorescent reporters for cell cycle phases [40].…”
Section: One Species Of Annual Killifish Has Recently Become a Relatimentioning
confidence: 99%
See 1 more Smart Citation
“…EVL arises at mid-blastula stage (2.5 hours post fertilization; hpf) covering the whole embryo 5 . During epiboly EVL maintains tight joins to the yolk syncytial layer (YSL), and becomes the migration substrate for the underlying deep cells spreading during gastrulation 6 . At the tail bud stage (8–10 hpf), the epiblast forms the outer germ layer, the ectoderm, characterized as a pseudo-epithelial germ layer.…”
Section: Introductionmentioning
confidence: 99%
“…E-cadh is required for blastomeres adhesion during the cleavage stage and later during gastrulation and epiboly 1921 . Indeed, as epiboly proceeds, EVL directs cell migration and the spreading of cells of the deep cells layer (DCL) in a process that requires dynamic cell contacts remodeling mediated by E-cadh 6 . Once the bi-layered epidermis is established, E-cadh role becomes more refined by keeping its integrity while actively remodeling cell-cell contacts within each layer.…”
Section: Introductionmentioning
confidence: 99%